2002
DOI: 10.1128/jvi.76.3.1015-1024.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Late-Domain-Containing Protein p6 Is the Predominant Phosphoprotein of Human Immunodeficiency Virus Type 1 Particles

Abstract: The Gag-derived protein p6 of human immunodeficiency virus type 1 (HIV-1) plays a crucial role in the release of virions from the membranes of infected cells. It is presumed that p6 and functionally related proteins from other viruses act as adapters, recruiting cellular factors to the budding site. This interaction is mediated by so-called late domains within the viral proteins. Previous studies had suggested that virus release from the plasma membrane shares elements with the cellular endocytosis machinery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 67 publications
1
58
0
Order By: Relevance
“…In HIV-1 particles, p6 also exist as a highly phosphorylated protein that is modified at Ser, Thr, and Tyr residues (20). Subsequently, it was shown that p6 becomes phosphorylated at position Thr-23 by the cellular mitogen-activated protein kinase ERK-2, which is also incorporated into mature virions, and appears to regulate L-domain function of p6 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HIV-1 particles, p6 also exist as a highly phosphorylated protein that is modified at Ser, Thr, and Tyr residues (20). Subsequently, it was shown that p6 becomes phosphorylated at position Thr-23 by the cellular mitogen-activated protein kinase ERK-2, which is also incorporated into mature virions, and appears to regulate L-domain function of p6 (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been implicated in the incorporation of the viral Pol and Env proteins (16,17) and in the control of particle size (18,19). Recently, p6 was reported to be the major phosphoprotein of HIV-1 particles (20), and there is evidence that the host cell mitogen-activated protein kinase ERK-2 regulates viral assembly and release by phosphorylation of Thr-23 in p6 (21).…”
mentioning
confidence: 99%
“…High titer HIV-1 preparations (ϳ10 9 infectious units/ml) containing minimal cellular contaminants were obtained from acutely infected MT-4 cells and purified by velocity gradient centrifugation (36). The purity of the sample was evaluated on silver-stained SDS gels, which showed that the Gag proteins were the main constituents and demonstrated minimal contamination with cellular proteins (data not shown) (55).…”
Section: Tsg101 Proteins Lacking the Vps28-binding Site Fail Tomentioning
confidence: 99%
“…HIV-1 virions were found to contain several phosphoproteins including MAp17 gag (13), CAp24 gag (14), and recently p6 gag proteins (15).…”
mentioning
confidence: 99%